Gambaran Compassion (For Others) Remaja Kristen di Jakarta - Hizkia Augustinus; Joshua Ong; Kartika C. Kirana (STT Iman Jakarta, 2020)
This study aims for understanding compassion among Christian adolescents in Jakarta since it interested in the levels to which participants can be compassionate to others. By then, compassion in this study is defined as a sensitivity to suffering in others (engagement) with a commitment to try to alleviate and prevent it (action). The sample consists of 102 Christian adolescents in Jakarta, aged between 16 and 24 years (Mage = 20). Participants were asked to fill out an Indonesian adaptation questionnaire of The Compassion Engagement and Action Scales. The results confirm that compassion levels of Christian adolescents in Jakarta are considerably medium, with a mean value of 70.81. Additional analyses using demographic data and single questions indicated that compassion levels are related to the adolescents’ perception of parental and community compassion, life satisfaction, and birth order.AbstrakPenelitian ini bertujuan untuk mengetahui gambaran compassion (for others) remaja Kristen di Jakarta, yaitu untuk melihat sejauh mana partisipan dapat berperilaku compassionate kepada orang lain. Karena itu, compassion didefinisikan sebagai perasaan tersentuh yang timbul dari kesadaran yang mendalam terhadap penderitaan orang lain (engagement) serta keinginan untuk meringankan penderitaan tersebut (action). Sample dalam penelitian ini terdiri dari 102 orang remaja Kristen di Jakarta berusia antara 16 sampai 24 tahun (Mage = 20). Untuk mengukur tingkat compassion, partisipan diminta untuk mengisi kuesioner adaptasi bahasa Indonesia dari The Compassion Engagement and Action Scales. Hasil penelitian menemukan bahwa tingkat compassion remaja Kristen di Jakarta tergolong menengah, yaitu dengan nilai mean sebesar 70.81. Uji tambahan juga menemukan bahwa compassion remaja terkait dengan penilaian atas besaran compassion orangtua, compassion lingkungan, dan kepuasan hidup, serta bahwa terdapat perbedaan tingkat compassion, khususnya dimensi engagement pada anak sulung dengan anak tunggal maupun anak tengah.